Contribuţii privitoare la viaţa şi activitatea lui Ienăchiţă Văcărescu - Eugenia Dima (Revista de Istorie și Teorie Literară)
In the paper the author deals with some unclear or even unknown aspects connected with the activity of the great Romanian scholar Ienăchiţă Văcărescu: 1. As a result of the linguistic and stylistic comparison between the texts known to belong to Văcărescu and the Pravilniceasca Condică, law code published in 1780 at the request of prince Alexandru Ipsilante, she has reached the conclusion that the text in Romanian is the work of Ienăchiţă Văcărescu. 2. The same contrastive method used on the available texts, especially the translation of the Hatişeriful Sultanului Selim, of 1791, allowed the author to establish, based on linguistic and textological similarities, the paternity of Ienăchiţă Văcărescu on the Romanian translation of the Hatişeriful Sultanului Hamid, of 1774. 3. Starting from previous researches connected to the Wallachian version of the Erotokritos by Vincenzo Cornaros, the author considers that the poem [Într-un copaci zarifior], attributed to Ienăchiţă, is extracted from the translation of the Erotokritos by Alecu Văcărescu and therefore the verses belong to his son. The motif of the falk caught in love’s chains is to be found in the Greek original and in the Moldavian version of its translation. 4. Citing a credible document, the author proves that the exact date of death of the great scholar is the 11th July 1797. 5. The annex at the end of the paper includes the edited text of the two Hatişerifuri, translated by Ienăchiţă Văcărescu, followed by an index of less known words.